A new species of Pleurothallis (Orchidaceae: Pleurothallidinae) in subsection Macrophyllae-Fasciculatae found in Carpish Montane Forest Regional Conservation Area, Peru - Ocupa-Horna, Luis; Wilson, Mark; Jiménez, Marco M. (Phytotaxa, 2023)
A new species of Pleurothallis belonging to subsection Macrophyllae-Fasciculatae was discovered in the Carpish Montane Forest Regional Conservation Area, Huánuco, Peru. Pleurothallis carpishensis is described, illustrated, and compared to P. radula, from which it is differentiated by the flowers borne from a depressed spathaceous bract resting on a navicular concavity on the leaf, the oblong-lanceolate, apiculate petals, with large papillae on the margins, the triangular, subacute lip, with a basal, widely ovate and emarginate, papillose-verrucose callus, with two oblique, lateral and marginal keels.